Model Distribusi Bahan Baku Asam Sulfat di PT XYZ dengan Metode Goal Programming - Diwanti Faradiba, Nabila; Wulandari, Indah Apriliana Sari; Sukmono, Tedjo; Putra, Boy Isma (Universitas Muhammadiyah Sorong, 2024)
The distribution of sulfuric acid raw materials is still conducted conventionally and faces challenges regarding the quantity of supply for each product. Therefore, this research was conducted to help create a mathematical model for the distribution of sulfuric acid using the Goal Programming method with the assistance of LINGO 18.0 software. Goal Programming serves to minimize deviations from limits and targets based on priorities in order to maximize profit and achieve the optimal quantity of sulfuric acid in the distribution of sulfuric acid raw materials, as well as to supply several fertilizers containing sulfuric acid. The research results indicate that the annual sales revenue target of 982,937,304 USD was achieved without any deviations. Most of the optimal production targets for products X1 to X8 were also met, with deviation variables showing no shortfall in production quantities for these products. However, for product X2, there remains a production shortfall of 60,096.15 tons to reach the target of 405,823 tons.